Resolución de problemas y su relación con el desarrollo de competencias matemáticas en estudiantes de secundaria (2021)
The main objective of this research is to determine the relationship between problem solving and the development of mathematical competencies in ninth grade students of the German Vargas Cantillo Educational Institution. In the development of the study, a diagnosis is made, through the application of a survey to establish, on the one hand, if the ninth-grade students present an adequate management of mathematical competencies to solve problems in the classroom of class and on the other hand, identifying, if problem solving is a strategy that favors the development of mathematical competencies. The results show that the students and teachers of the educational institution studied are aligned with the procedures and principles required for the proper development of problem solving in the classroom and outside of it, because they have had into account, all those concomitant and necessary elements, in accordance with the current educational regulations, the standards of competence in mathematics at the international and national level, and what the theory in this regard establishes, in terms of problem solving and their positive characterization in relation to mathematical skills. It is concluded that the problem-solving process potentiates operational capacities and cognitive abilities within and outside the educational context, therefore, the knowledge itself and the development of said procedure, strengthens the apprehension of mathematical competencies in students. students.